Internet of things and its applications to marathon events: from the prospect of sport tourism and urban development. (14th July 2022) - Leou, Eusebio C.; Ruan, Rachel M.; Yu, Runze
The Internet of things (IoT) is a new frontier that is growing in areas of healthcare, sports and wellness, as well as sports events. However, the application of IoT is developing and has rarely been investigated. It seems there would be more room for its application in sport events. This study tried to describe the application of IoT technology in sports events. The authors adopted marathon events as an example and illustrated how IoT accommodated with sport events to improve participants' sport involvement and satisfaction, and its impact on the willingness to return of those visitors of sport events. The authors observed marathon events participants by using Interpretative Phenomenological Analysis (IPA), and the resulting application of IoT in marathon events as a stimulus to enhance satisfaction and sport involvement of participants. Marathon participants are willing to re-participant sport events due to IoT technology is advantageous elements for themselves.